2005
DOI: 10.1007/s00125-004-1646-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal clearance of glycolaldehyde- and methylglyoxal-modified proteins in mice is mediated by mesangial cells through a class A scavenger receptor (SR-A)

Abstract: Aims/hypothesis: Glomerular mesangial expansion is a characteristic feature of diabetic nephropathy, and the accumulation of AGE in the mesangial lesion has been implicated as one of its potential causes. However, the route for the AGE accumulation in mesangial lesions in diabetic patients is poorly established. Methods: Glycolaldehyde-modified BSA (GA-BSA) and methylglyoxalmodified BSA (MG-BSA) were prepared as model AGE proteins, and their in vivo plasma clearance was examined in mice, and renal uptake by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Protein labeling with 125 I. AOPPs-HSA and HSA were labeled with 125 I by Iodo-Gen (Pierce), as previously described (35). A solution containing 10 l of Na 125 I solution and 0.5 mg of proteins in 0.2 ml of 0.1 M sodium phosphate buffer (pH 7.4) in an Iodo-Genadhered test tube was incubated for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Protein labeling with 125 I. AOPPs-HSA and HSA were labeled with 125 I by Iodo-Gen (Pierce), as previously described (35). A solution containing 10 l of Na 125 I solution and 0.5 mg of proteins in 0.2 ml of 0.1 M sodium phosphate buffer (pH 7.4) in an Iodo-Genadhered test tube was incubated for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the DJ‐1 family member Hsp31 was observed to degrade MG‐modified proteins having a deglycase‐like function . Kidney eliminates a major part of circulating AGE and dicarbonyl adducts, as after filtration they are reabsorbed by the tubular and mesangial cells, degraded in the lysosomes and eliminated as AGE‐amino acids …”
Section: The Promise Of New Therapeutic Targetsmentioning
confidence: 99%
“…56) Interestingly, we recently found that advanced glycation end product albumins, produced by reacting albumin with glucose or reducing sugar are cleared from the kidney by scavenger receptor A-mediated endocytic uptake by mesangial cells. 57) Extracorporeal Clearance using HSA Albumin can be used to clear the body of certain endogenous toxins. Among these are bilirubin, bile acids, and uremic toxins.…”
Section: Drug-albumin Binding In Disease Statesmentioning
confidence: 99%